2002
DOI: 10.1139/z02-015
|View full text |Cite
|
Sign up to set email alerts
|

To heat or to save time? Thermoregulation in the lizardZootoca vivipara(Squamata: Lacertidae) in different thermal environments along an altitudinal gradient

Abstract: Behavioural regulation of body temperature in thermally heterogeneous habitats requires different amounts of time that could otherwise be dedicated to foraging and social activities. In this study I examined how four populations of the lizard Zootoca vivipara along an altitudinal gradient (250-1450 m) adjust their thermal-physiology traits and thermoregulatory behaviour to compensate for increasing time costs of thermoregulation. I focused on variation in several physiological (set-point temperature, heating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
83
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 51 publications
6
83
2
2
Order By: Relevance
“…Similar responses are observed in other reptiles. For example, in the viviparous common lizards (Zootica vivipara), females from high altitude populations spend 50% more time basking than those from low altitudes (Gvozdik, 2002), while in the oviparous water dragons (Physignatus lesueurii), mothers dig nests more superficially at high altitude than at low altitude, thus compensating for the climatic differences between altitudes (Doody et al, 2006;Doody, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar responses are observed in other reptiles. For example, in the viviparous common lizards (Zootica vivipara), females from high altitude populations spend 50% more time basking than those from low altitudes (Gvozdik, 2002), while in the oviparous water dragons (Physignatus lesueurii), mothers dig nests more superficially at high altitude than at low altitude, thus compensating for the climatic differences between altitudes (Doody et al, 2006;Doody, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, local adaptations in maternal effects should be common in widespread species (e.g. Gvozdik, 2002;Doody et al, 2006;Doody, 2009). In viviparous reptiles it remains unclear, however, whether populations that have evolved in different climatic conditions will exhibit locally adapted maternal basking behaviour or locally adapted gestational thermal effects on offspring development.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that lizards from cooler habitats can compensate the high cost of thermoregulation by increasing basking time and using microhabitats differentially (HERTZ & ZOOLOGIA 27 (1): 13-18, February, 2010 HUEY 1981, CHRISTIAN et al 1983, DUNHAM et al 1989, ADOLPH & PORTER 1993, 1996, BAUWENS et al 1996. Additionally, lizards can change body posture and/or body orientation to the sun (BAUWENS et al 1996, GVO•DÍK 2002, and change activity patterns ( VAN DAMME et al 1989, BAUWENS et al 1996. Phymaturus palluma showed a clear sex difference in activity patterns, but not in T b .…”
Section: Discussionmentioning
confidence: 99%
“…The idea that different species of lizards maintain a certain "optimal" temperature was predominant until the mid-20 th century; however, it has since then been shown that there is no single optimal temperature but rather several optima depending on the activity (Rocha et al 2009). The extent of thermoregulation is also known to vary intraspecifically due to various factors, such as altitude (Gvoždík 2002), seasonality (Huey and Pianka 1977), habitat structure (Sears and Angilletta 2015), sex , or even competition with other species (Žagar et al 2015). Moreover, an individual may be a thermal specialist at specific times but a thermal generalist overall throughout the year (Angilletta 2009).…”
Section: Introductionmentioning
confidence: 99%